Akibat Hukum Yang Timbul Terhdap Tanah Yang Sudah Di Hibahkan Kemudian Di Jual Kembali - Rizal Bobihu; Weny Almoravid Dungga; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2023)
Land is very beneficial for human life and is a gift from God Almighty. Human life and land are closely intertwined. Humans need a piece of land not only to survive but also to die. As a result, land scarcity is increasingly appearing, even though the need for land is increasing. For human existence, land is an essential component. This is due to population growth which increases every year in direct proportion to the need for land. A number of strategies are used by the community to manage, own, and even trigger land conflicts. This shows that land also has rights, has social purposes, and that the public interest overrides private interests in its use. All land rights have social uses, according to Article 6 of Law Number 5 of 1960 concerning Basic Agricultural Regulations or UUPA. A grant is the gift of an item to someone where the giver is still alive. This study aims to determine the legal status of land that has been donated and then resold and what are the legal consequences arising from the land that has been granted and then resold, in Putiana Village, Orchid District, North Gorontalo Regency in a review of Law Number 5 of 1960. Based on the results of the research it is understood that the withdrawal of gift items according to the Civil Code is regulated in article 1688 which reads that a grant cannot be revoked and therefore cannot be revoked, except in 3 cases, namely if the grantee's conditions are not fulfilled by the recipient of the grant, if the person the person who was given the grant is guilty of committing or participating in an attempt to kill or some other crime against the donor himself, and if the grantor falls into poverty while the one who was given the gift refuses to provide for him. If the recipient of the grant refuses to provide a living or allowance to the grantor, after that the grantor falls into poverty. With the withdrawal or elimination of this gift, all kinds of items that have been donated must be returned to the grantor in a clean condition of the burdens attached to the item. The legal consequence of the decision to cancel a grant that has permanent legal force is that the object of the dispute, namely land, will return to the grantor and their rights. If the object of the dispute has been certified on behalf of the recipient of the grant, then with this decision the certificate becomes null and void.